The Application of Logical Tools in Project-Based Classrooms - Jakovljević, Marija (Oeconomica Jadertina, 2017)
The purpose of this paper is to investigate the application of logical tools such as inference trees and columnar data flow diagrams in the information system (IS) analysis and design context. Seventeen students at an institution of higher education were observed during the design and analysis of information systems and their experiences were evaluated through a focus group interview, observations and documents analysis. This research was based on a qualitative, action research approach (Yin 1994; Merriam 1998). The most important findings were: the columnar method empowers students’ motivational and cognitive skills enhancing their vision and system design skills; inference trees improve detection and correction of reasoning errors overcoming students’ limited information processing capacity.